Two rivalries in the Umma (1-11AH) and their implications for the interpretation of the Sira literature - Gould, James Frederick (The University of Edinburgh, 1975)
This thesis is an attempt to clarify, and hence to understand, two of the rivalries which were disunifying factors in the umraa of Medina during the lifetime of Muhammad. The divisive qualities of the Ansar and the Munafiqun have, in the past, been ignored and only their influence upon the religious development of Islam has been examined. The rivalry between the Ansar and the Kuhajirun of Quraysh was the origin of the great north/south rivalry which plagued the Islamic empire in the centuries to come, although the seeds of the dispute may be found in the Jahiliya. There remains very little historical evidence of this rivalry although on one occasion it was sufficiently serious to suggest that a minor incident might have provoked a full scale civil war. When it was realized that the Muslims were going to be successful in their conflict with the Quraysh, the Ansar became more resigned to their fate although the election of Abu Bakr indicated that they were not yet reconciled to their position as second class citizens. A study of the historical activities of the Munafiqun indicates that the English word 'hypocrite' does not adequately translate the more complex connotations of the word Munafiq. Their rivalry with the other Muslims was another facet of the struggle of the Madinese against the domination of the Quraysh. They focused the resentment of the Ansar and acted as an internal opposition party until it was realized that victory was impossible. They have been portrayed as the villains of Islamic history and their name has been blackened to an extent which is not justified by a careful study of the available information. The story of their withdrawal from the Muslim army on the route to Uhud is held as an example of their perfidy and yet it seems certain that the story was a later creation designed to shift the blame for the defeat from Muhammad. The Munafiqun represented the traditional values of Madinese society and as such were closely allied to the Jewish tribes. When Muhammad finally joined the pro-Arab faction of Medina they allied themselves to the Jewish faction out of a desire to maintain the status quo. Ibn Ubayy was the leader of the Munafiqun and as such has been vilified by the Muslim historians. During the Jahiliya he had been one of the leading figures of Medina and he continued to play this role after the Hijra, championing the rights of the Madinese against the Quraysh. His early conversion led to a final reconciliation with Muhammad as evidenced by the Prophet praying for him. He failed in his objective of retaining power in the face of the threat posed by Islam because he and the Munafiqun were unable to offer an ideology which could cope with the cnanging society of the community. By accepting a principle of independent action as a tenet of belief he was unable to maintain a body of support upon which he could rely. With the loss of his Jewish allies his failure was complete. Muhammad was forced to control the two rivalries in order to preserve the existence of the umrna. In many ways he acted as a- traditional tribal leader but, by virtue of the fact that he was also the Messenger of God, he was able to apply innovative methods which had never been used effectively in Arabia. Unity was not finally achieved until after his death; however, by the emphasis which was placed upon it the basis was laid for the later expansion of Islam. Prom the study of the rivalries certain implications as to the beginnings of historical writing among the Arabs can be drawn, especially in relation to the biography of Muhammad. m The Islamic bias of the historians should have precluded the inclusion of all but a small portion of the material which relates to the rivalries; however, it did not. It may be concluded that the material was retained in explanation of the descent of Qur'anic verses and to glorify the person of Muhammad. By analysing the basic accounts of some incidents there is an obvious development seen in the handling of the material until the time of al-Tabari when tafsir was divorced from history. Ibn Ishaq had expected his readers to be conversant with the verses of the Qur'an and al-Waqidi had felt it necessary to add a more detailed explanation. It is obvious from the texts that there were other rivalries and disunifying factors in the umma, but any records of them have been removed as unnecessary for the understanding of the Qur'an and as unsuitable for the image of Muhammad as it was conceived in the years after his death. It is also certain that there were other outbreaks of the rivalry between the groups under study in this thesis which have been omitted for the same reasons.
A study of two rivalries in the Umma (1-11AH) and their implications for the interpretation of the Sira literature